Implementing Islamic Education Management to Foster a Healthy Lifestyle Culture: A Case Study of Pesantren Miftahul Mubtadiin Krempyang, Nganjuk - M. Munir (Pascasarjana Manajemen Pendidikan Islam STAI Darussalam Nganjuk, Indonesia, 2025)
This research looked at how a specific Islamic boarding school in Nganjuk (Pesantren Miftahul Mubtadiin Krempyang) uses organized management methods based on Islamic principles to get its students living healthier lives. The study acknowledges that while these schools are great for overall student growth, making health a core part of traditional boarding life can be tough. The researchers talked to people, observed daily life, and looked at school documents. They found that the school uses Islamic management steps (like planning health programs and organizing them) and strongly links health activities to Islamic values (e.g.,